How Do Collegiate Sport Clubs Achieve Organizational Effectiveness? - Leeann M. Lower-Hoppe; Shea Brgoch; Richard Bailey; Ashley Ryder; Chad Lowe; Stephen Dahl; Daniel Wray (Journal of Applied Sports Management, 2020)
A greater understanding of the organizational processes of sport clubs can inform strategies to improve clubs’ organizational effectiveness. This study examined whether sport club capacity and activities influence the organizational effectiveness of collegiate sport clubs. Sport club members (n = 201) completed a questionnaire, with secondary data collected from the university. Regression analysis found club operations, club fiscal responsibility, frequency of club practice, and frequency of competitions significantly, positively predict organizational effectiveness. Comparatively, club human capital and facility quality significantly, negatively predict organizational effectiveness. These results have implications relating to club training, mentorship, resource allocation, and club activities.
Keywords: Capacity; Management; Multiple Constituency Model; University Administration